1273. Activity of Ceftolozane/Tazobactam and Comparators Against Enterobacterales and P. aeruginosa Isolates from Pediatric Patients—SMART United States 2017-2019. (4th December 2021) - Lob, Sibylle; Hackel, Meredith; Andrew DeRyke, C; Harris, Kelly; Young, Katherine; Motyl, Mary; Sahm, Daniel F
Abstract: Background: Ceftolozane/tazobactam (C/T) is an antipseudomonal cephalosporin combined with a β-lactamase inhibitor approved by FDA and EMA for complicated urinary tract (cUTI) and complicated intraabdominal infections (cIAI), as well as hospital-acquired/ventilator-associated bacterial pneumonia (HABP/VABP) in patients ≥18 years. Clinical trials studying the use of C/T for pediatric patients with cUTI and cIAI are completed, and HABP/VABP pediatric studies are underway. We evaluated the antimicrobial activity of C/T against gram-negative isolates collected from patients ≤17 years in the United States (US) as part of the global SMART surveillance program. Methods: In 2017-2019, 27 US clinical labs each collected up to 250 consecutive gram-negative pathogens per year. A total of 1336 isolates were collected from pediatric patients. MICs were determined using CLSI broth microdilution and breakpoints. C/T-nonsusceptible Enterobacterales (Ebact) and P. aeruginosa were screened for genes encoding β-lactamases. Results: Among the 944 collected Ebact and 220 P. aeruginosa isolates, 40.7% and 76.4%, respectively, were collected from patients with respiratory tract infections, 37.0% and 10.0% from UTI, 13.7% and 8.2% from IAI, and 8.3% and 5.0% from bloodstream infections. The table shows antimicrobial susceptibility of Ebact, P. aeruginosa, and select phenotypes. C/T was active against 98% of Ebact, including 50 of 51 and 12 of 13 ESBL-non-CRE phenotype E. coli and K. pneumoniae, respectively. Among P. aeruginosa, C/T was active against 95% of isolates, 9-21 percentage points higher than the comparator β-lactams, and it maintained activity against 71-75% of P. aeruginosa isolates nonsusceptible to commonly used β-lactams. Among the 21 C/T-nonsusceptible Ebact, 2 isolates carried KPC and ESBL and 3 isolates carried only ESBL; in 16 isolates no β-lactamases were detected, of which 15 were species with intrinsic AmpC. Among 12 C/T-nonsusceptible P. aeruginosa, no acquired β-lactamases were detected, likely indicating chromosomally-mediated resistance mechanisms. Results Table Conclusion: C/T could be a potential new treatment option for US pediatric patients with infections caused by Ebact and P. aeruginosa, including resistant phenotypes. Disclosures: Sibylle Lob, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) C. Andrew DeRyke, PharmD, Merck & Co., Inc. (Employee, Shareholder) Kelly Harris, PharmD, BCPS, Merck & Co. Inc (Employee) Katherine Young, MS, Merck (Employee) Mary Motyl, PhD, Merck & Co., Inc. (Employee, Shareholder) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)